Rapid and Sensitive Direct Detection of Endotoxins by Pyrolysis–Gas Chromatography–Mass Spectrometry - Jackie, Jackie (ACS Omega, 2021)
[Image: see text] The capability of pyrolysis–gas chromatography–mass spectrometry (Py–GC–MS) for the direct analysis of endotoxins is demonstrated in this research article using the lipopolysaccharides of Pseudomonas aeruginosa 10. Analytical methods based on evolved gas analysis–MS, single-shot (SS) Py–GC–MS, and multishot heart cut Py–GC–MS were investigated. Among the various methods developed, the SS Py–GC–MS method shows superior potential for identifying bacterial endotoxins effectively through their biomarkers. The results obtained were validated with conventional mass spectral analysis after hydrolysis. The method was also evaluated for its robustness based on quality control criteria indicated by the U.S. EPA Method 8270D. When applied onto endotoxins of different Gram-negative bacteria, this method produced vastly distinct pyrograms. The results show that rapid and sensitive direct detection of endotoxins is possible with the Py–GC–MS method developed.